Repair of critical-size defects with autogenous periosteum-derived cells combined with bovine anorganic apatite/collagen: an experimental study in rat calvaria - Paulo, Anderson de Oliveira [UNESP]; Castro-Silva, Igor Iuco; Oliveira, Davi Ferreira de; Machado, Manoel Eduardo de Lima; Bonetti-Filho, Idomeo [UNESP]; Granjeiro, José Mauro (Fundação Odontológica de Ribeirão Preto, 2011)
O objetivo deste estudo foi avaliar o reparo ósseo usando células derivadas de periósteo (PDC) e apatita inorgânica e colágeno bovinos (HA-COL). PDC de ratos Wistar (n=10) foram semeadas sobre discos de HA-COL e osteoinduzidas por 6 dias. Defeitos de tamanho crítico em calvárias de ratos foram tratados com coágulo sanguíneo (G1), osso autógeno (G2), HA-COL (G3) ou HA-COL associado a PDC (G4) (n=40) e analisados em 1 e 3 meses após as cirurgias. Análise radiográfica não exibiu mudança temporal significante, G1 e G2 tiveram aumento discreto de novo osso marginal, entretanto a radiopacidade dos materiais de enxerto em G2, G3 e G4 prejudicou a detecção de osteogênese. Análise histopatológica mostrou em 3 meses ilhotas de ossificação em G1 que foi maior em G2, novo osso homogêneo ao redor de HA-COL em G3 e novo osso heterogêneo ao redor de HA-COL em G4 além da presença moderada de células gigantes de corpo estranho em G3 e G4. Análise histomorfométrica mostrou a densidade de volume inalterada do xenoenxerto (p>0,05) e a densidade de volume de novo osso em G2 duas vezes maior que G1 e G4 após 3 meses (p<0,05), mas similar a G3. PDC não aumentaram a formação óssea in vivo apesar do biomaterial sozinho ter apresentado biocompatibilidade e capacidade osteocondutora.

The aim of this study was to evaluate the bone repair using autogenous periosteum-derived cells (PDC) and bovine anorganic apatite and collagen (HA-COL). PDC from Wistar rats (n=10) were seeded on HA-COL discs and subjected to osteoinduction during 6 days. Critical-size defects in rat calvarias were treated with blood clot (G1), autogenous bone (G2), HA-COL (G3) and HA-COL combined with PDC (G4) (n=40), and then analyzed 1 and 3 months after surgeries. Radiographic analysis exhibited no significant temporal change. G1 and G2 had discrete new marginal bone, but the radiopacity of graft materials in G2, G3 and G4 impaired the detection of osteogenesis. At 3 months, histopathological analysis showed the presence of ossification islets in G1, which was more evident in G2, homogeneous new bone around HA-COL in G3 and heterogeneous new bone around HA-COL in G4 in addition to moderate presence of foreign body cells in G3 and G4. Histomorphometric analysis showed no change in the volume density of xenograft (p>0.05) and bone volume density in G2 was twice greater than in G1 and G4 after 3 months (p<0.05), but similar to G3. The PDC did not increase bone formation in vivo, although the biomaterial alone showed biocompatibility and osteoconduction capacity.
Keywords: critical size defects; periosteum-derived cells; xenograft; hydroxyapatite; collagen